A flexible field-limited ordered ZnO nanorod-based self-powered tactile sensor array for electronic skin. Issue 36 (30th August 2016) - Deng, W.; Jin, L.; Zhang, B.; Chen, Y.; Mao, L.; Zhang, H.; Yang, W.
Abstract : A flexible self-powered tactile sensor for multi-point touch control and display. Abstract : A tactile sensor is an essential component for realizing biomimetic robots, while the flexibility of the tactile sensor is a pivotal feature for its application, especially for electronic skin. In this work, a flexible self-powered tactile sensor array was designed based on the piezoelectricity of ZnO nanorods (NRs). The field-limited ordered ZnO NRs were synthesized on a flexible Kapton substrate to serve as the functional layer of the tactile sensor. The electrical output performances of the as-fabricated tactile sensor were measured under pressing and bending forces. Moreover, we measured the human-finger pressure detection performance of the tactile sensor array, suggesting that the corresponding mapping figure of finger pressure could be displayed on the monitor of a personal computer (PC) in the form of lighted LED and color density through a LabVIEW system. This as-grown sensory feedback system should be of potential valuable assistance for the users of hand prostheses to reduce the risk and obtain a greater feeling of using the prostheses.